Mainstreaming climate change adaptation into inland aquaculture policies in Thailand - Anuwat Uppanunchai (2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. While there have been many pilot projects on adaptation undertaken in the fisheries and aquaculture sector, state policies are only just beginning to address let alone refer to climate change. This study explores the climate-related content, climate sensitivities, and opportunities to incorporate climate change concerns in a set of aquaculture policies by the government of Thailand. The analysis is based on content analysis of policy documents and in-depth interviews with 14 officials that had roles in the design or implementation of 8 Department of Fisheries policies. The Aquaculture Master Plan 2011–2016 and the now abandoned Tilapia Strategy refer directly to climate variability or change. The Master Plan also suggests measures or strategies, such as investment in research, and the transfer of technologies, which would be helpful to sustainability and adaptation. Other policies suggest, or at the very least include, practices which could contribute to strengthening management of climate-related risks, for example: a registration policy included provisions for compensation; extension programme policy recognizes the importance of extreme events; and a standards policy gives guidance on site selection and water management. Most existing aquaculture policies appear to be sensitive to the impacts of climate change; for instance, the zoning policy is sensitive to spatial shifts in climate. Stakeholders had ideas on how policies could be made more robust; in the case of zoning, by periodically reviewing boundaries and adjusting them as necessary. POLICY RELEVANCE This study is one of the first evaluations of the coverage and sensitivity of aquaculture policies to climate change. It shows that while existing policies in Thailand are beginning to refer explicitly to climate change, they do not yet include much in the way of adaptation responses, underlining the need for identifying entry points as has been done in this analysis. Further mainstreaming is one option; another possibility is to adopt a more segregated approach, at least initially, and to collect various policy ideas under a new strategic policy for the aquaculture sector as a whole.